Highly efficient green InP/ZnSe/ZnS quantum dots synthesized using tris(diethylamino)phosphine - Seongrae Kim; Jiwan Kim (Journal of Information Display)
Indium phosphide (InP) quantum dots (QDs) have shown great potential as an alternative for cadmium-based QDs in optoelectronic applications. However, the development of green InP QDs using non-toxic precursors remains a pressing challenge to efficient device performance. This study synthesized green InP/ZnSe/ZnS QDs using tris(diethylamino)phosphine as a phosphorous precursor and optimized their synthesis conditions for superior photoluminescence quantum yield (90%) and narrow emission spectra (37 nm). Quantum dot light-emitting diodes (QLEDs) with green InP multishell QDs achieved a peak luminance of 1862.7 cd/m² and a current efficiency of 3.5 cd/A. Despite promising results, further optimization of isotropic QD growth and charge transport in device structure is necessary to enhance overall device performance, highlighting the potential of InP-based QDs for future display technologies.